Lessons learnt from the IWRM demonstration projects: innovations in local-level integrated water resource development in Malawi, Mozambique, Swaziland and Zambia - van Koppen, Barbara; Chisaka, J.; Shaba, S.S. (SADC/Danida Water Sector Support Programme, 2009)
This report presents seven innovations in Local-level Integrated Water Resource Management, based on lessons learnt in the IWRM Demonstration Projects in Malawi, Mozambique, Swaziland and Zambia.